A case of primary duodenal Brunner's gland hamartoma that gradually underwent morphological changes over a period of 10 years - Yusuke Sunada; Hiromichi Yamane; Nobuaki Ochi; Hirohito Kirishi; Takako Saitou; Masafumi Miura; Hidekazu Nakanishi; Hideyo Fujiwara; Nagio Takigawa (DEN Open)
Abstract Brunner's gland hamartoma (BGH) is a benign tumor occurring in the duodenal bulb. BGH is typically asymptomatic, but it has been shown to occasionally cause anemia. The patient was a 76‐year‐old male. In October 2011, he was diagnosed with prostate cancer with multiple bone metastases and was referred to us for the treatment and examination of anemia. Hormonal therapy with androgen receptor antagonists and bisphosphonate administration following orchiectomy improved his symptoms. In August 2012, esophagogastroduodenoscopy (EGD) was performed due to stomach discomfort, revealing a 5 mm semi‐pedunculated polyp in the duodenal bulb, Yamada‐Fukutomi classification type II. Over the next 5 years, the prostate cancer treatment proceeded smoothly, and no endoscopic follow‐up was conducted. In January 2017, during a health checkup, EGD revealed that the polyp in the duodenum bulb had changed morphologically with a distinct stalk measuring 10 mm. As there were no symptoms and only minimal tumor growth, a watchful waiting approach was adopted. In April 2022, due to the rapid progression of anemia, EGD was performed again, showing that the pedunculated polyp had enlarged to 20 mm in maximum diameter with an eroded surface and a stalk extending to 40 mm. Given the tumor enlargement and further examination of anemia, an endoscopic polypectomy was performed in May 2022. Histopathological examination confirmed the diagnosis of BGH. We observed a case of primary duodenal BGH during treatment for advanced prostate cancer, with endoscopic monitoring over 10 years. The morphological changes of BGH were clearly documented via EGD.